Prohormone convertase 2 (PC2) null mice have increased mu opioid receptor levels accompanied by altered morphine-induced antinociception, tolerance and dependence. (4th August 2016) - Lutfy, K.; Parikh, D.; Lee, D.L.; Liu, Y.; Ferrini, M.G.; Hamid, A.; Friedman, T.C.
Highlights: Prohormone convertase 2 (PC2) processes prohormones to extended opioids. Chronic morphine treatment increases the expression of PC2. PC2 null mice had higher brain levels of mu opioid receptors. PC2 null mice exhibited enhanced morphine-induced antinociception. Morphine tolerance and naloxone-precipitated withdrawal were attenuated in these mice. Abstract: Chronic morphine treatment increases the levels of prohormone convertase 2 (PC2) in brain regions involved in nociception, tolerance and dependence. Thus, we tested if PC2 null mice exhibit altered morphine-induced antinociception, tolerance and dependence. PC2 null mice and their wild-type controls were tested for baseline hot plate latency, injected with morphine (1.25–10 mg/kg) and tested for antinociception 30 min later. For tolerance studies, mice were tested in the hot plate test before and 30 min following morphine (5 mg/kg) on day 1. Mice then received an additional dose so that the final dose of morphine was 10 mg/kg on this day. On days 2–4, mice received additional doses of morphine (20, 40 and 80 mg/kg on days 1, 2, 3, and 4, respectively). On day 5, mice were tested in the hot plate test before and 30 min following morphine (5 mg/kg). For withdrawal studies, mice were treated with the escalating doses of morphine (10, 20, 40 and 80 mg/kg) for 4 days, implanted with a morphine pellet on day 5 and 3 days later injected with naloxone (1 mg/kg) and signs of withdrawal were recorded. Morphine dose-dependently induced antinociception and the magnitude of this response was greater in PC2 null mice. Tolerance to morphine was observed in wild-type mice and this phenomenon was blunted in PC2 null mice. Withdrawal signs were also reduced in PC2 null mice. Immunohistochemical studies showed up-regulation of the mu opioid receptor (MOP) protein expression in the periaqueductal gray area, ventral tegmental area, lateral hypothalamus, medial hypothalamus, nucleus accumbens, and somatosensory cortex in PC2 null mice. Likewise, naloxone specific binding was increased in the brains of these mice compared to their wild-type controls. The results suggest that the PC2-derived peptides may play a functional role in morphine-induced antinociception, tolerance and dependence. Alternatively, lack of opioid peptides led to up-regulation of the MOP and altered morphine-induced antinociception, tolerance and dependence.